2013
DOI: 10.11118/actaun201260050027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional parameters of native apple cultivars as new gene sources

Abstract: BALÍK, J., ROP, O., MLČEK, J., HÍC, P., HORÁK, M., ŘEZNÍČEK, V.: Assessment of nutritional parameters of native apple cultivars as new gene sources. Acta univ. agric. et silvic. Mendel. Brun., 2012, LX, No. 5, pp. 27-38

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A total of 63,407,407 metric tons of apple worth approximately $23.5 billion are consumed yearly [ 1 , 2 , 3 ]. Apple is very popular as a healthy fruit and it contains multiple minerals, vitamins, and phytochemicals, including carotenoids, flavonoids, polyphenolic compounds, and phenolic acids [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Apple juices are also important dietary sources of these bioactive compounds [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 63,407,407 metric tons of apple worth approximately $23.5 billion are consumed yearly [ 1 , 2 , 3 ]. Apple is very popular as a healthy fruit and it contains multiple minerals, vitamins, and phytochemicals, including carotenoids, flavonoids, polyphenolic compounds, and phenolic acids [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Apple juices are also important dietary sources of these bioactive compounds [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peel of varieties 'Apistar', 'Bobovac' and 'Božićnica' could be highlighted as an important source of polyphenols.These compounds are studied intensively in epidemiological research, because they have a positive impact on human health through the prevention of cardiovascular diseases and cancer, the regulation of plasma cholesterol metabolism, antiviral properties, the inhibition of Helicobacter pylori growth and staphylococcal enterotoxin A toxicity [7][8][9]. It has been suggested that traditional apples contain higher amounts of polyphenols when compared to commercial ones [2,[10][11][12][13][14][15]. In addition, it is well known that apple peel, as a by-product of apple processing, contains a higher polyphenolic content and antioxidant capacity than apple flesh [2,16,17].Currently, the extraction of phenolic compounds from fruit by-products attracts great attention.…”
mentioning
confidence: 99%